Unsteadiness of the rotor slipstream in the ground effect and its impact on helipad loads - Ruchala, P. (My University, 2022)
The concept of elevated (rooftop) heliport is known and developed for decades. However due to the significant noise and other drawbacks of helicopters, their application in practice is currently limited mostly to emergency cases, like the lifesaving. Secondly, in recent years the idea of autonomic, light and quiet air taxies flying to cities gains in interests. Such vehicles would need some amount of free space to land and take-off safely; the rooftop heliports seem to be perfectly suitable. A drawback of the elevated heliports may be vibrations of the whole building, caused primarily by the unsteadiness of the rotor slipstream impinging on the heliport surface during take-off and landing. It is especially awkward in case of medical heliports, due to strict vibration requirements. On the other hand, oscillations of loads caused by a helicopter rotor slipstream are quite unappreciated issue. To investigate this topic, an experimental investigation focused on a remotely controlled, 450-class helicopter, has been performed. Measurement of pressure acting on the simulated heliport plate showed a level of pressure oscillations for different test cases, as a function of radial position. The Fourier analysis has also been performed to show dominant frequency of the oscillation. Moreover, the velocity field in the rotor slipstream was captured using PIV method to capture the tip vortices position, to explain the low-frequency component of the oscillation.